Validação de conteúdo da versão brasileira digital do children's anxiety questionnaire - Santos, Gabriely Silva dos [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Introduction: The anxiety experienced by children due to hospital experience, whose environment is unknown to the child, often causes a negative interference in treatment and procedures performed and satisfaction is reduced. The use of validated instruments and audiovisual resources for pediatric patient care is relevant for nursing decision making and critical analysis of care systematization. Objective: The objective of this study was to validate the content of the digital version of the Children's Anxiety Questionnaire (CAQ) with nurses from a university hospital. Method: A multicenter research is being conducted at Hospital das Clínicas da Faculdade de Medicina de Botucatu (HCFMB) and Hospital Geral de Palmas. However, for the present analysis only one of the stages, carried out at HCFMB, is included. This is a methodological research that was carried out following the fifth stage proposed by Beaton (2007), called pre-test with the target audience. The CAQ is a Swedish instrument for assessment of anxiety in hospitalized children by means of a one-dimensional scale. The evaluation for validation of the technological instrument was performed by the participating nurses by means of an online structured questionnaire. Fifty-eight nurses who work in pediatric care were invited via e-mail and Whatsapp, of whom 26 agreed to participate. For data analysis, the content validity index (CVI) was used, which measures the proportion or percentage of judges who are in agreement, and a cut-off score, CVI equal to 0.80, was employed. Results: The digital Children's Anxiety Questionnaire instrument was content-validated by experts from one of the institutions participating in the study with experience in pediatric care, with an overall Content Validity Index of 0.95, suggesting that it is relevant to pediatric practice. Final Considerations: As a contribution, the CAQ may be used as an audiovisual tool by nurses working in pediatric care, aiming to measure anxiety self-reported by children, since the instrument enables children to verbalize positive and negative feelings, in addition to helping monitor changes in children's behavior during the period of treatment or hospitalization.

Introdução: A ansiedade vivenciada por crianças devido a experiência hospitalar, cujo ambiente é desconhecido para a criança, causa muitas vezes, uma interferência negativa no tratamento e nos procedimentos realizados e a satisfação é reduzida. O uso de instrumentos validados e recursos audiovisuais para atendimento do paciente pediátrico, é relevante para a tomada de decisão em enfermagem e auxílio na análise crítica da sistematização da assistência. Objetivo: O objetivo deste trabalho é realizar a validação de conteúdo da versão digital do Children 's Anxiety Questionnaire (CAQ) com enfermeiros de um hospital universitário. Método: Uma pesquisa multicêntrica está sendo conduzida no Hospital das Clínicas da Faculdade de Medicina de Botucatu (HCFMB) e Hospital Geral de Palmas. No entanto, para a presente análise inclui-se somente uma das etapas,que foi realizada no HCFMB. Trata-se de uma pesquisa metodológica que foi realizada seguindo a quinta etapa proposta por Beaton (2007), denominada pré-teste com o público-alvo. O CAQ é um instrumento Sueco, para avaliação da ansiedade em crianças hospitalizadas por meio de uma escala unidimensional. A avaliação para validação do instrumento tecnológico foi realizada pelos enfermeiros participantes por meio de um questionário estruturado online. Foram convidados 58 enfermeiros que atuam na assistência pediátrica, via e-mail e Whatsapp, dos quais 26 aceitaram participar. Para a análise dos dados foi utilizado o índice de validade de conteúdo (IVC) que mede a proporção ou porcentagem de juízes que estão em concordância, onde empregou-se uma pontuação de corte, o IVC igual a 0,80. Resultados: O instrumento digital Children’s Anxiety Questionnaire foi validado em conteúdo por especialistas de uma das instituições participantes do estudo com experiência na área da assistência pediátrica, com um Índice de Validade de Conteúdo Global de 0,95, sugerindo que é relevante para a prática pediátrica. Considerações Finais: Como contribuição, o CAQ poderá ser utilizado como uma ferramenta audiovisual por enfermeiros que atuam na assistência pediátrica, com o objetivo de mensurar a ansiedade autorreferida por crianças, visto que o instrumento possibilita que as crianças verbalizam sentimentos positivos e negativos, além de auxiliar a monitorar mudanças de comportamento da criança durante o período de tratamento ou hospitalização
Content validation of the brazilian digital version of the children's anxiety questionnaire
Keywords: Children; Pediatric nursing; Measurement instruments; Nursing process; Validation instrument; Crianças; Enfermagem pediátrica; Instrumentos de medida; Processo de enfermagem; Instrumento de validação